A Simple Model of Globalization, Schooling and Skill Acquisition - Carl Davidson; Nicholas Sly (Center for Economic Studies and ifo Institute (CESifo), 2013)
We develop a model of schooling and skill acquisition, highlighting informational asymmetries that distort the incentives to educate. A key feature of our model is that education acts simultaneously as a signaling device and as a method for workers to enhance their productivity. We show that when firms can only imperfectly screen workers, the result is an economy in which too many workers purchase schooling and too few workers devote sufficient effort to their coursework to qualify for the high skill labor pool. We then examine how greater openness to international markets alters the skill mix of the domestic workforce and show that greater openness usually eases one labor market distortion while making the other distortion worse. Globalization impacts educational behavior and labor market outcomes differently as the extent of firms engaged in international markets varies, and affects wage inequality both within and across educational groups.
Keywords: 330